Pengaruh Gaya Kepemimpinan Kepala Madrasah Dan Pembina OSIS Terhadap Populasi Organisasi Siswa Intra Sekolah Di Madrasah Tsanawiyah Hidayatul Mubtadiin Sidoharjo Jati Agung Lampung Selatan - Uyun, Karimah Nur; Sarpendi, Sarpendi; Rohmawati, Zulfa (Penerbit Widina, Widina Media Utama, 2026)
This study aims to examine the relationship between the leadership patterns of the madrasah principal and the OSIS advisor with the development of the intra-school student organization population at the Hidayatul Mubtadiin Sidoharjo Islamic Junior High School, Jati Agung, South Lampung, both separately and together. This study specifically describes the role of the madrasah principal in shaping the level of student activity through a flexible, communicative, and inspiring leadership approach, and examines the function of the OSIS advisor as a companion who directs the course of daily organizational activities. The study used a quantitative design with a survey method that was conducted in September 2025 at MTs Hidayatul Mubtadiin Sidoharjo, Jati Agung, South Lampung. The research subjects included all 15 members of the IX grade OSIS and were determined as samples using a total sampling technique. Data collection was carried out through a closed-ended Likert-scale questionnaire that had passed validity and reliability tests. Data were analyzed using simple linear regression and multiple regression, preceded by testing the assumptions of normality and homogeneity to assess the influence of the leadership of the madrasah principal and the OSIS advisor on OSIS dynamics. The results of the analysis indicate that the leadership of the madrasah principal and the OSIS advisor at MTs Hidayatul Mubtadiin Sidoharjo tends to be negatively related and does not show statistical significance to the OSIS population. The findings of the regression and partial tests indicate that increasing leadership intensity has not directly impacted the increase in the number or activity of OSIS members. This condition suggests that changes in the OSIS population are more influenced by other factors, such as internal student motivation, organizational culture, social interaction patterns, and the level of readiness and maturity of the student organization. The transformational, participatory, and situational leadership frameworks emphasize that leadership effectiveness rests on the quality of communication, empowerment practices, and the suitability of leadership style to the character of the members. Thus, although the impact of leadership has not been shown to be statistically significant, the role of leadership remains strategic in building a healthy and sustainable student organization climate.ABSTRAKPenelitian ini diarahkan untuk menelaah keterkaitan antara pola kepemimpinan kepala madrasah dan pembina OSIS dengan perkembangan populasi organisasi siswa intra sekolah di Madrasah Tsanawiyah Hidayatul Mubtadiin Sidoharjo, Jati Agung, Lampung Selatan, baik ditinjau secara terpisah maupun bersama-sama. Kajian ini secara spesifik menguraikan peran kepala madrasah dalam membentuk tingkat keaktifan siswa melalui pendekatan kepemimpinan yang fleksibel, komunikatif, dan memberi dorongan inspiratif, serta menelaah fungsi pembina OSIS sebagai pendamping yang mengarahkan jalannya aktivitas organisasi sehari-hari. Penelitian menggunakan desain kuantitatif dengan metode survei yang dilaksanakan pada September 2025 di MTs Hidayatul Mubtadiin Sidoharjo, Jati Agung, Lampung Selatan. Subjek penelitian mencakup seluruh anggota OSIS kelas IX yang berjumlah 15 siswa dan ditetapkan sebagai sampel dengan teknik total sampling. Pengumpulan data dilakukan melalui kuesioner tertutup berskala Likert yang telah melalui uji validitas dan reliabilitas. Data dianalisis menggunakan regresi linier sederhana dan regresi berganda, didahului pengujian asumsi normalitas dan homogenitas untuk menilai pengaruh kepemimpinan kepala madrasah dan pembina OSIS terhadap dinamika OSIS. Hasil analisis menunjukkan bahwa kepemimpinan kepala madrasah dan pembina OSIS di MTs Hidayatul Mubtadiin Sidoharjo cenderung berhubungan negatif dan tidak menunjukkan signifikansi statistik terhadap populasi OSIS. Temuan regresi dan uji parsial mengindikasikan bahwa peningkatan intensitas kepemimpinan belum secara langsung berdampak pada bertambahnya jumlah maupun keaktifan anggota OSIS. Kondisi ini mengisyaratkan bahwa perubahan populasi OSIS lebih banyak dipengaruhi oleh faktor lain, seperti dorongan internal siswa, budaya organisasi, pola interaksi sosial, serta tingkat kesiapan dan kematangan organisasi siswa. Kerangka kepemimpinan transformasional, partisipatif, dan situasional menekankan bahwa efektivitas kepemimpinan bertumpu pada kualitas komunikasi, praktik pemberdayaan, serta kesesuaian gaya kepemimpinan dengan karakter anggota. Dengan demikian, meskipun dampak kepemimpinan belum terlihat signifikan secara statistik, peran kepemimpinan tetap memiliki posisi strategis dalam membangun iklim organisasi siswa yang sehat dan berkelanjutan.